Accelerated ageing versus realistic ageing in aerospace composite materials. IV. Hot/wet ageing effects in a low temperature cure epoxy composite - Dao, B; Hodgkin, J.H; Krstina, J; Mardel, J; Tian, W (Journal of applied polymer science, 2007)
Samples of an aerospace grade carbon fiber epoxy composite (Hexcel, M20/IM7) were subject to long term ([almost equal to]1 year) hot/wet ageing and thermal spiking under a variety of humidity levels and temperature conditions related to "in service" conditions seen by military aircraft. Changes to the chemical and physicochemical structure of the composite were analyzed by a range of different techniques including gravimetric analysis, FTIR, and DMA to compare the effects of the various ageing conditions. The results indicated that the chemical effects of hot/wet and spiking conditions on this incompletely cured type of composite are very complex because of the variations in moisture levels and cure chemistry from the composite surface inwards as the resin ages under the different external environments. Physicochemical changes (such as Tg) and structural effects (such as microcracking) are similarly complex and dependent on composite thickness. © 2007 Wiley Periodicals, Inc. J Appl Polym Sci 2007